Passing plays leading to passing and dribbling plays in the 16th fiba women`s world championships - Sakuragi, K.; Aoyagi, O.; Komure, I.; Tagata, S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: Preceding passing plays are related to subsequent passing and dribbling plays in basketball games. The present study aimed to identify relationships between preceding passing plays and subsequent passing and dribbling plays. Methods: We analyzed 1084 pairs of preceding passing plays and subsequent passing and dribbling plays implemented by six teams at the 16th FIBA Women`s World Championships. The following passing and dribbling plays were assessed: forward passes that moved the ball to the back court (cf); passes that changed the side or angle to create a scoring opportunity in the back court (cc); before-shooting passes (aa); passes leading to a one-on-one situation (ab); passes leading to a driving play (ac); passes to the postman (pa); passes to change the angle (po); passes from the top to the side to change the side (s); return passes to the guard or top (rt); passes to the corner (cn); hand-in passes (hh); throw-ins (p); dribbling to move the ball to the back court (cd); dribbling on the spot in the front court (fco); and so on. A cross-table of preceding passing plays with subsequent passing and dribbling plays was then generated. The x^2 test was applied to the cross-table, and an adjusted residual was computed if a significant difference was identified. Significant relationships were found between preceding passing plays and subsequent passing and dribbling plays with a significantly larger adjusted residual. Results: The results of the x^2 test were significant at the 0.1% level (x^2 = 5685.22; df = 260). We found cells with >20 frequencies and a significant adjusted residual in cf > cd (frequency, 94; adjusted residual, 7.31), cf > cc (147, 19.20), pa >aa (20, 5.25), po > ab (24, 18.22), po > pa (23, 13.82), s > rt (133, 8.55), s> cn (71, 11.88), s > aa (55, 3.53), s > pa (44, 3.83), s > hh (38, 5.54) and so on. Discussion: In the absence of defensive pressure, a long pass from the back court to the front court is considered to be most effective passing play (cf > cd, cc). When the ball was passed to the post player, the defensive player was obliged to focus on the post, but not their matching offensive player. This situation caused space to be created around all offensive players other than the post player, and each offensive player could thus easily assist their teammates (pa > aa). Changing the angle of the passing course is more effective for creating one-on-one situations and passing to the post player (po > ab, pa). An offensive team that wants to restart an offense often applies the strategy of changing the ball-side (c >rt and cn). On the contrary, changing the offensive ball-carry side is more effective for breaking through a defense, and thus offensive players can easily perform aa, hh, and pa (s >aa, hh,pa).